Pengaruh Suku Bunga Kredit dan Risiko Kredit terhadap Return On Asset dengan Pendapatan Bunga sebagai Variabel Intervening - Sely Megawati Wahyudi; Nona Lice Pota Buga (Faculty of Economic and Business, 2020)
This study was conducted to examine the effect of lending rates, net performance loans, interest income on return on asset (ROA). The population in this study is a finance company listed on the Stock Exchange in 2015-2019. The sample was determined by a porposive sampling method – 65 samples. The data used are secondary data obtained from the IDX gallery. The hypothesis in this study was tested using path analysis to determine the direct and indirect effects of the independent variables used on the dependent variable. The results of this study indicate that partially lending rates have a significant influence on interest income, while credit risk which is proxied by Net Performance Loan (NPL) has no significant effect on Interest Income. Credit Interest Rates do not have an effect on Return On Assets (ROA), while Credit Risk which is proxied by Net Performance Loan (NPL) has a significant negative effect on Return On Assets (ROA) and Interest Income has a significant positive effect on Return On Asset (ROA). The indirect relationship between lending rates and credit risk with Return On Assets (ROA) by using interest income as an intervening get significant results.